Community Empowerment through Health Promotion Regarding Prevention of the Spread of COVID-19 in East Java - Linda Presti Fibriana; Nuris Kushayati; Heti Aprilin; Anik Supriani; Nasrul Hadi Purwanto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
ABSTRACT Organization (WHO) as a pandemic, namely a disease that is transmitted globally (global outbreak). The Covid-19 pandemic as a non-natural disaster is becoming increasingly